Pembelajaran Matematika Dengan Media Jam Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Pengukuran Waktu - Maria Mei Wulandari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to determine the effect of using clock media on students' level of understanding of time measurement material compared to learning that does not use clock media. The subjects used in this research were class 2 students with a total of 10 students, 6 male students and 4 female students at SD Negeri 1 Sengon, Prambanan District. The indicators used in this research are the duration for students to understand concepts and problem solving skills. Using clock media for students' understanding of the material taught in time measurement material can be more effective and efficient. This is shown by an increase in learning outcomes based on pre-cycle completion with a percentage of 48%, cycle 1 and cycle 2 with a percentage of 63% and 86%. So it can be concluded that this model can improve mathematics learning outcomes in time material in class II A at SD Negeri 1 Sengon